2021
DOI: 10.1089/can.2020.0037
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and the Gut–Brain Axis Communication in HIV Infection

Abstract: People living with HIV infection (PWH) disclose that cannabis is an effective strategy for alleviating symptoms associated with HIV disease. However, some medical providers feel ill-informed to engage in evidence-based conversations. HIV leads to alterations in the gut microbiome, gut-brain axis signaling, and chronic inflammation. The endocannabinoid system regulates homeostasis of multiple organ systems. When deficient, dysregulation of the gut-brain axis can result in chronic inflammation and neuroinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 105 publications
0
10
0
Order By: Relevance
“…This may be particularly relevant in the context of the endocannabinoid system, as the endocannabinoid system regulates homeostasis of multiple organ systems, including the gut. Because dysregulation of the gut-brain axis can result in chronic inflammation and neuroinflammation, endocannabinoids have anti-oxidant, and anti-inflammatory properties relevant to modulation of inflammation that occurs along the gut-brain axis ( 101 , 102 ).…”
Section: Endocannabinoid Pain Biomarkersmentioning
confidence: 99%
“…This may be particularly relevant in the context of the endocannabinoid system, as the endocannabinoid system regulates homeostasis of multiple organ systems, including the gut. Because dysregulation of the gut-brain axis can result in chronic inflammation and neuroinflammation, endocannabinoids have anti-oxidant, and anti-inflammatory properties relevant to modulation of inflammation that occurs along the gut-brain axis ( 101 , 102 ).…”
Section: Endocannabinoid Pain Biomarkersmentioning
confidence: 99%
“…Further, since ECS regulates homeostasis of the gut microbiome, HIV leads to alterations in the gut microbiome and gut-brain axis signaling, as well as chronic inflammation and neuroinflammation. Thus, it has been suggested that cannabis, or CBD that potentially has antioxidant and anti-inflammatory properties, may be used as an adjunct therapy in healing and restoring the gut microbiome in HIV-infected subjects [58]. However, more clinical research is needed to collect evidence that would support the use of CBD in the treatment of these inflammatory disorders.…”
Section: Cannabis and Infectionsmentioning
confidence: 99%
“…Several other aspects of chronic marijuana use in people living with HIV are unknown or understudied, including its association with symptoms of pain and anxiety, problems such as cannabis use disorder, and biological responses such as chronic inflammation [ 32 , 33 ]. There is evidence linking marijuana use with a decreased inflammatory response [ 11 , 17 , 18 ], but no reports to date have examined this relationship using longitudinal data.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term effects of marijuana use on people living with HIV are not clear and could potentially vary across individuals and by variation in cannabinoid type and strength within different strains of marijuana and medical marijuana products. Δ9-tetrahydrocannabinol (THC) is the most psychoactive component of marijuana, whereas some evidence suggests that other components of cannabis, such as cannabidiol (CBD) and various terpenes, or their combinations, show more promise for medical treatments [10,11]. In some studies, marijuana use has been shown to alleviate HIV-related symptoms, such as loss of appetite, fatigue, anxiety, neuropathy, pain, nausea, systemic inflammation, neurocognitive impairment, and gastrointestinal problems, and medication side effects [5,[11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation